Peningkatan Kemampuan Pra Braille Melalui Penggunaan Media Papan Pantule Bagi Siswa Tunanetra Kelas I di SLB Bhakti Luhur Baumata Kupang - Eko, Yohana; Selan, Ot Bil Wilson; Wangge, Vinsensius (Indo-MathEdu Intellectuals Journal, 2026)
This classroom action research aimed to improve the pre-Braille skills of two first-grade visually impaired students at SLB Bhakti Luhur Baumata Kupang through the use of a "pantule" board (a tactile pegboard). The study employed the Kemmis and McTaggart model comprising planning, action, observation, and reflection stages and was conducted over three cycles. The subjects were two seven-year-old visually impaired students: IK, who is totally blind, and MD, who has multiple visual impairments. Data were collected via observation, assessment tests, interviews, and documentation, then analyzed using both qualitative and quantitative descriptive methods. The results demonstrated a gradual improvement in pre-Braille skills. In Cycle I, IK scored 51.8 and MD scored 49.2, with a class mastery rate of 0%. In Cycle II, IK’s score rose to 72, meeting the mastery criteria, while MD’s score increased to 55.8, bringing the class mastery rate to 50%. In Cycle III, which focused on MD, the score improved to 67, and the class mastery rate reached 100%. In the context of this study, the use of the pantule board facilitated improvements in pre-Braille skills—including tactile sensitivity, fine motor coordination, tactile discrimination, and directional concepts which serve as the foundation for Braille learning. These findings are specific to the research subjects and cannot yet be generalized to all visually impaired students